Losing a Family Member in Earthquake: The Mediating Role of Fear of Intimacy Between Family Cohesion and Mental Well-Being - Korun, Ali Berke; Satici, Seydi Ahmet (SAGE PUBLICATIONS INC, 2025)
Earthquakes are unpredictable disasters that have catastrophic consequences and caused many people to lose their family members. In this study, the relationships between family cohesion, fear of intimacy and mental well-being were examined in individuals who lost a family member after the 6 February 2023 Kahramanmara & scedil; earthquakes. The study included 385 participants (Mean = 20.56; SD = 2.43) and structural equation modelling used. According to findings, family cohesion positively affected mental well-being and fear of intimacy negatively affected mental well-being. In addition, fear of intimacy partially mediated the relationship between family cohesion and mental well-being. These results emphasize the importance of family dynamics in post-disaster mental health. Strengthening family cohesion after traumatic events may increase both relationship skills and mental well-being. Based on a family systems approach, this study suggests that post-disaster interventions should focus on strengthening family cohesion to improve both relational and mental health outcomes for individuals.
Keywords: family cohesion; fear of intimacy; mental wellbeing; earthquake; DEPRESSION; SURVIVORS; Psychology; Biomedical Social Sciences